Chronotopoi of the Good Life and Utopia: Bakhtin on Goethe's Bildungsroman Wilhelm Meister and the carnivalesque. Issue 9 (29th July 2017) - Franke, Norman
Abstract: This paper explores Bakhtin's reception of Goethe's Wilhelm Meisters Lehrjahre with a view to assess how Bakhtin's interest in this early chronotopical masterpiece can be understood in the wider context of his utopian thinking and his political eschatologies. Bakhtin reads Goethe's novel as a critique of totalitarian forms of Socialist Realism as well as Dostoyevsky's bourgeois realism. Like his contemporary Ernst Bloch, Bakhtin praises the complexity and richness of Goethe's concept of realism. In the wake of Hermann Cohen, Georg Simmel and Friedrich Gundolf to whom Bakhtin alludes and whom he quotes, Goethe is regarded as a modern literary and anthropological role model, the epitome of Bildung. For Bakhtin, Goethe's and Rabelais' writings about the carnivalesque constitute complementary forms of reflection of and agents for social and cultural transformation in modernity.